An outline for the history of social psychology in Croatia: people and trends - Čorkalo Biruški, Dinka (2007)
Major developmental trends of the Croatian social psychology has been presented with emphasis on European and American influences and a unique contribution of the Croatian psychological tradition.
Projekt MZOS
ENG